The Effect of Post-mastectomy Radiotherapy in Patients With Metaplastic Breast Cancer: An Analysis of SEER Database - Wang, Jun; Zhang, Wen-Wen; Lian, Chen-Lu; Sun, Jia-Yuan; He, Zhen-Yu; Wu, San-Gang (Frontiers in Oncology, 2019)
Introduction: Metaplastic breast cancer (MBC) is a rare and aggressive form of breast cancer. The present study aimed to assess the effect of postmastectomy radiotherapy (PMRT) in MBC patients with intermediate-risk (T1-2N1M0 and T3N0M0) and high-risk (T1-4N2-3M0 and T4N0-1M0) disease. Methods: The Surveillance, Epidemiology and End Results database was used to analyze patients with MBC between 2000 and 2014. Kaplan–Meier analysis, log-rank tests, and the multivariate Cox proportional model were used for statistical analysis. Results: We identified 460 patients with a median follow-up time of 31 months (range, 2–178 months). Five-year breast cancer specific survival (BCSS) for all patients was 57.5%. In the entire group, multivariate analysis showed that PMRT was associated with better BCSS (hazard ratio (HR) 0.500, 95% confidence interval (CI) 0.366–0.683, P < 0.001). The 5-year BCSS in PMRT and non-PMRT groups were 62.3% and 50.3%, respectively (P = 0.001). When stratified the patients into intermediate-risk and high-risk groups, PMRT could improve BCSS compared with that in non-PMRT patients in both the intermediate- and high-risk groups. For the intermediate-risk group, the 5-year BCSS was 74.3% and 64.7% in PMRT and non-PMRT groups (P = 0.042), respectively, and was 52.1% and 28.8% in high-risk patients treated with PMRT and non-PMRT, respectively (P<0.001). Conclusion: PMRT could improve the BCSS of MBC patients with intermediate- and high-risk disease.